Relationship Pattern of Fishermen and Employers In Kepenghuluan Panipahan Laut, Pasir Limau Kapas District Rokan Hilir Regency, Riau Province - Khoirunnisak '; Firman Nugroho; Zulkarnain ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted at November 2016 in Kepenghuluan Panipahan Laut district Pasir Limau Kapas, Rokan Hilir regency, Riau province. The purpose of this research is to know the relationship pattern between fisherman and the employer and to know the benefit of this relation. The method that used in this research is qualitative phenomenological method. The informants of this research are twelve fishermen and three employers. So, total of the informants are fifteen people.According to the result of the research, relationship pattern between the fishermen and the employers in Kepenghuluan Panipahan Laut has some elements, which are work relationship element pattern that happened because of there are activities between fishermen and employers, social relationship element that happened by social interacting in economic relationship and economic relationship element that happened by economic activity and personal relationship element that happened from that social interaction. The benefits to the fishermen are fishing equipment are helped, fishermen daily needs, this relationship give a guarantee (sense of security) to the fishermen in provision of capital and marketing. While, the benefits to the employers are stock of the fish won’t stop so that employers economic will stable and employers can monopolize the price of the fish.Key words: Fisherman, Employer, Panipahan Laut